Zależność i niezależność od pola a przyswajanie języka angielskiego. Wyniki badania pilotażowego oraz analiza zastosowanych procedur i narzędzi badawczych - Jantarska, Anna (Neofilolog, 2019)
The aim of this article is to present the results of a pilot study and to verify its methodological and statistical procedures. The subject matter of the study in question is the relationship between the cognitive styles of field dependence (FD)/field independence (FI) and the level of second language proficiency. The reader is presented with the wide range of variables and instruments incorporated in the study. The findings demonstrate strong correlations between the subjects’ FD/FI mode of perceiving the world and the results of language tests. The findings indicate that the relationship between dependent and independent variables is modified by age and sex of the subjects.